Growing Menace of Antibacterial Resistance in Clinical Isolates of Pseudomonas aeruginosa in Nepal: An Insight of Beta-Lactamase Production. (23rd August 2016) - Ansari, Shamshul; Dhital, Rabindra; Shrestha, Sony; Thapa, Sangita; Puri, Ram; Chaudhary, Niraj; Khatiwada, Suresh; Gautam, Rajendra
Abstract : Introduction. Pseudomonas aeruginosa is the most frequently isolated organism as it acts as the opportunistic pathogen and can cause infections in immunosuppressed patients. The production of different types of beta-lactamases renders this organism resistant to many commonly used antimicrobials. Therefore, the aim of this study was to document the antibiotic resistance rate in Pseudomonas aeruginosa isolated from different clinical specimens. Methods. Pseudomonas aeruginosa recovered was identified by standard microbiological methods. Antibiotic susceptibility testing was performed by modified Kirby-Bauer disc diffusion method following Clinical and Laboratory Standard Institute (CLSI) guidelines and all the suspected isolates were tested for the production of ESBLs, MBLs, and AmpC. Results. Out of total (178) isolates, 83.1% were recovered from the inpatient department (IPD). Majority of the isolates mediated resistance towards the beta-lactam antibiotics, while nearly half of the isolates were resistant to ciprofloxacin. Most of the aminoglycosides used showed resistance rate up to 75% but amikacin proved to be better option. No resistance to polymyxin was observed. ESBLs, MBLs, and AmpC mediated resistance was seen in 33.1%, 30.9%, and 15.7% isolates, respectively. Conclusions . Antibiotic resistance rate and beta-lactamase mediated resistance were high. Thus, regular surveillance of drug resistance is of utmost importance.